Peculiarities of Personal Self-Improvement in Early and Late Adolescence - Gorbaniuk, Julia; Serhіeіenkova, Oksana; Yablonska, Tetiana (Social Welfare: Interdisciplinary Approach, 2018)
The article analyzes the peculiarities of personal self-improvement in early and late adolescence. The age, individual psychological and gender characteristics of adolescents influencing their real and ideal self-images, the directions of desired changes and selfimprovement motivation are revealed. The peculiarities of self-improvement of girls and boys are characterized; self-improvement tendencies during the specified age periods are analyzed. The process of personal self-improvement has distinct individualpsychological colors, which is determined primarily by the peculiarities of personal characteristics, self-awareness and motivations.
Keywords: self-improvement; self-development; self-knowledge; ideal self; real self